The Pattern of Drug Abuse in Anonymous Adidcts - Seyede Maryam Vahdat-S; Shahin Shahbazi (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: Having the information about pattern of substance abuse in the community and its epidemiological features is one of the most important protocols for evaluation, follow-up and control of the use of these substances. The aim of this study was to evaluate the patterns of substances abuse among narcotic anonymous (N. A. ) addicted patients. Materials & Methods: In this descriptive and analytical study, three hundred patients from narcotic abusers anonymous (N. A. ) association who were referred to a treatment center in Tehran were participated consecutively. The information about demographic characteristics, socioeconomic status, type of drug and the patterns of substance abuse of all cases were collected by researcher made questionnaire. Data were analyzed by Chi-Square test. Results: 80% of the patients were male. Almost 65. 2% of cases aged less than 40 years. More than two-third of cases had free jobs and 21. 2% of them were unemployed. Also, 32% of patients had college degrees. The most common types of abused substance were opium (88%), cigarette (76.7%), and alcohol (63%) and 34% of them used substances intravenously. The use of alcohol (P=0.033), cannabis (P<0.001), cocaine (P=0.009) and ecstasy (P<0.001) was more prevalent significantly in the cases less than 40 years old than the elderly. Conclusion: It seems that the trend of substance abuse has been changed to younger population. The pattern of drug abuse in young adults is more toward psychosis drugs such as cocaine and ecstasy.